MODIFIKASI TENAGA POMPA MENJADI SISTEM HAMPA UDARA PADA ALAT VERTIKULTUR - Hilmaturrifqi, Hilmaturrifqi; Yanto, Subari; Patang, Patang (Jurnal Pendidikan Teknologi Pertanian, 2017)
This study aimed to determine distributioninput and output capacity of water on the vacuumsâ€™ shelter and the impact of cultivation system in developing vertikultur device ofÂ  pumpenergy. This research is a design building. The data that collected consist of hydrostatic pressure (P), input and output capacity of water distribution, water discharge, plant height and plant production. The data was analyzed by using descriptive analysis. The results showed that the water circulation occurred because P1> P2 with the value of each pressure was P1 4900 kg/ms2 and P2 1960 kg/ms2, the average of inputdistribution capacity was 202.5 ml/sec while the distribution of water output capacity was 184.5 ml / sec, the average of water discharge as long as output experiment was 0,32 ml/sec and input 0,39 ml/sec. Then this device was applied to the kale plant.